An overview of the current research programmes in Protective Technology Research Centre at NTU - Pan, Tso-Chien (2011)
This paper presents a host of research activities currently conducted at the PTRC. The main objective is to introduce the research programmes to the protective engineering community in this conference. All of these works are sponsored by the Defence Science Technology Agency (DSTA), Singapore. The paper starts off with progressive collapse research which involves the testing and simulation of critical reinforced concrete structural elements to ascertain two reserve load-carrying mechanisms viz. catenary action and tensile membrane action when one or two perimeter columns are forcibly removed. These are the last line of defence mechanism just before progressive collapse kicks in. This paper introduces an experimental programme conducted on alternate load paths under two critical scenarios: External and penultimate column loss scenarios. Some test results involving slabs, beam-to-column joints, sub-frames and columns will be presented in the light of missing-column scenarios. The numerical capabilities of the centre will also be presented. These include (i) modelling of the break-up of uncovered and earth-covered RC magazine under internal high loading-density detonation, and (ii) concrete modelling for oblique perforation of slab by hard projectile. The last part of paper looks at the Underground Technology and Rock Engineering (UTRE) programme, which is a joint research programme between the Protective Technology Research Centre and DSTA. The UTRE programme aims to advance underground technologies in (i) rock dynamics research, (ii) discontinuous displacement analysis and manifold method, (iii) a comprehensive database for underground constructions; (iv) continuous health monitoring system for underground caverns and tunnels; (v) and fire safety and evacuation research for underground structures. Due to the specialist nature of each research work, the paper omits most details but interested readers can refer to the references included at the end of this paper.